(untitled) (Third Sector Social Economic Review, 2025)
This study investigates the multifaceted effects of economic globalization on Türkiye’s economic growth over the period 1970–2020 using the Autoregressive Distributed Lag (ARDL) model. The empirical findings reveal that, in the long run, increased levels of economic globalization exert a statistically significant and negative impact on economic growth. This result contrasts with the predictions of endogenous growth theory, which posits that globalization fosters growth through knowledge spillovers. Conversely, variables such as gross fixed capital formation (lnGFCF) and trade openness (lnTA) demonstrate positive and statistically significant effects on growth, consistent with neoclassical and endogenous growth models. Specifically, a 1% increase in capital formation and trade openness enhances economic growth by approximately 0.41% and 0.47%, respectively. However, a 1% rise in the economic globalization index reduces growth by about 0.79%, highlighting the potential adverse effects of globalization, particularly in structurally vulnerable developing economies. These findings emphasize the necessity of complementing globalization with structural reforms and industrial policies aimed at reducing import dependency. Ultimately, while trade liberalization and investment promotion support Türkiye’s growth trajectory, minimizing the risks of globalization through sound macroeconomic strategies remains essential for long-term sustainable development.